الجمال الطبيعي والجمال الفني عن هيجل (Comprehensive Journal of Science, 2025)
This study aims to examine natural beauty and artistic beauty according to Hegel and analyze the reasons why Hegel prefers art over nature. The research begins with the concept of natural beauty, which focuses on harmony and sensory perception in nature and evokes visual pleasure, yet lacks intellectual and spiritual dimensions. Then, it moves to artistic beauty, representing the highest level of beauty, where the artwork unites form and content, allowing the artist to consciously express thought and spirit, achieving a connection between sensory matter and absolute idea.The study also discusses the reasons for Hegel’s preference for art over nature, including art’s ability to consciously express spirit and idea, empowering the artist with freedom and creativity, embodying spiritual and intellectual truth, and reflecting the development of human consciousness throughout history. The research concludes that, for Hegel, art is not merely sensory pleasure but a means of knowledge and contemplation, placing human awareness at the center of the aesthetic process and emphasizing the central role of art in developing human thought and spirit
Keywords: Natural beauty, artistic beauty, Hegel’s philosophy, art and spirit, artistic expression, form and content, artistic freedom, perception of truth.